2003
DOI: 10.1038/sj.cgt.7700569
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of adenovirus-uteroglobin transduction on the growth of lung cancer cell lines

Abstract: Uteroglobin is a secretory protein synthesized by most epithelia, including the respiratory tract. It has strong anti-inflammatory properties that appear to be related to the inhibition of phospholipase A2. Recent experimental evidence indicates that uteroglobin has an inhibitory effect on the proliferation and invasion of cancer cells. We investigated the effects of the adenovirusuteroglobin (ad-UG) transduction on the growth of lung cancer cell lines, which did not express the uteroglobin gene. Upon transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…23 Using adenovirus-uteroglobin (ad-UG) transducted lung cancer cell lines, which did not express the UGB gene, it has been shown that growth rates and colony-forming ability of the transformed cells were significantly reduced by the induction of UGB gene expression. 24 To our knowledge, there have been no previous reports regarding UGB expression changes in GBM. Mammaglobin, another member of the UGB family, attracted wide attention because of its potential as a clinical marker for breast metastases.…”
Section: Discussionmentioning
confidence: 91%
“…23 Using adenovirus-uteroglobin (ad-UG) transducted lung cancer cell lines, which did not express the UGB gene, it has been shown that growth rates and colony-forming ability of the transformed cells were significantly reduced by the induction of UGB gene expression. 24 To our knowledge, there have been no previous reports regarding UGB expression changes in GBM. Mammaglobin, another member of the UGB family, attracted wide attention because of its potential as a clinical marker for breast metastases.…”
Section: Discussionmentioning
confidence: 91%
“…It has been found that some of these genes were already found to be responsible for lung adenocarcinoma. For example, genes IGFBP3 [5,23], SFTPA1 [18,41], SFTPA2 [41], TNFAIP3 [12], TNFSF6 [4], TNFSF10 [43], UGB [54,24,22], HBB [31] were already found by some earlier investigations. We now describe, in brief, a few genes that are found to be responsible by the two methods.…”
Section: Validation Of the Results Obtained By Both Methods 1 And Methmentioning
confidence: 98%
“…The adenoviral construct (Ad-CC-10) is an E1 deleted, replication-deficient adenoviral type 5 vector (Ad5) encoding human CC-10 cDNA. The recombinant Ad-CC-10 was constructed as described previously (26). Briefly, the cDNA of human CC-10 was cloned into the adenoviral shuttle vector, pACCMVpLpA.…”
Section: Methodsmentioning
confidence: 99%
“…Transduction was accomplished using the standard method (2 h incubation at 37˚C), as described previously (26). The production of the CC-10 protein was assessed by ELISA specific for human CC-10, and a higher concentration was demonstrated with increasing MOI, showing a 10-fold increase in CC-10 protein secretion with 50 MOI and a 15-fold increase with 100 MOI compared with the negative control (Fig.…”
Section: Ad-cc-10 Gene-modified Human Dcs Produce Biologically Activementioning
confidence: 99%
See 1 more Smart Citation